Experimental and finite element studies on free vibration of skew plates - Srinivasa, Venkateshappa Chikkol; Suresh, Jayadevappa Y.; Prema Kumar, Wooday Puttiah (Zielona Góra: Uniwersytet Zielonogórski)
The present paper deals with the experimental studies carried out on free vibration of isotropic and laminated composite skew plates. The natural frequencies were also determined using QUAD8 finite element of MSC/NASTRAN and a comparison was made between the experimental values and the finite element solution. The effects of the skew angle and aspect ratio on the natural frequencies of isotropic skew plates were studied. The effects of the skew angle, aspect ratio, fiber orientation angle and laminate sequence (keeping the number of layers constant) on the natural frequencies of antisymmetric composite laminates were also studied.
Keywords: skew plates; antisymmetric laminates; free vibrations; experimental methods; finite element analysis